Dose-dependent reduction of lymphocyte count and heart rate after multiple administration of LC51-0255, a novel sphingosine-1-phosphate receptor 1 modulator, in healthy subjects - Hwang, Inyoung; Lee, Sang Won; Oh, Jaeseong; Lee, SeungHwan; Jang, In-Jin; Yu, Kyung-Sang (Frontiers in Pharmacology, 2022)
Aim: Sphingosine-1-phosphate receptor mediates egress of lymphocyte from lymphoid organs, and its inhibition results in decreased number of circulating lymphocytes. The aim of the current study was to investigate the safety, pharmacodynamic and pharmacokinetic characteristics of a novel spingosine-1-phosphate receptor modulator, LC51-0255. Methods: A phase 1 randomized, double-blind, placebo-controlled, multiple dosing, dose-escalation study was conducted in healthy Korean male subjects. Results: After single and daily administration of LC51-0255 for 21 days, dose-dependent decrease of lymphocyte count and heart rate was observed through LC51-0255 0.25 mg to 2 mg dose range. The mean elimination half-life of LC51-0255 was 76–95 hours. LC51-0255 was accumulated with mean accumulation ratio of 5.17–6.64. During the study, LC51-0255 was generally well-tolerated. The most common treatment-emergent adverse event (TEAE) was bradycardia. No clinically significant event of arrhythmia, including AV block, was observed. No clinically significant difference in blood pressure was observed between dose groups. In other safety assessments, no clinically significant abnormalities were observed, except for bradycardia. Conclusion: Daily administration of LC51-0255 in range of 0.25 mg to 2 mg resulted in dose-dependent reduction of lymphocyte counts and heart rate. LC51-0255 was generally safe and well-tolerated in healthy volunteers.